PENGARUH MODEL PEMBELAJARAN KOOPERATIF PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA - Ismiati Yusra; Dwi Putri Musdansi; Nofri Yuhelman (Universitas Islam Kuantan Singingi, 2020)
Hydrocarbon is a discusion topic in chemistery by bringing concept as key point. One ofsupporting learning methode for concept discovery is cooperative study project based learning.This type of reseach used in the study is experimental quasion with Non Equivalent ControlGroup Design. Samples were taken by using cluster random sampling technic. There two clasesfor this study wich are 18 students for experiment class and 20 students for control class. Theinstrument in this study was in the form of 20 multiple choise questiont that have been tested andtested by an instrument in the form of validity, different power, difficulty levels and reliability. Inthe reability test the value of cronbach’s alpha = 0,887 is obtained, meaning that the test has veryhigh reliability. So that 20 question were obtained for the post test. Independent Independent t-testis carried out for analysing technic. Based on hypothesis analysing with t-test, score sig (1- talled)= 0,001 < 0,005, it means H0 is unaccepted. The result of this analysis is Project Based Learningmodel is better than Teacher Center Learning to study hydrocarbon in class XI MIA MAN 2Kuantan Singingi.